Optimasi Produksi Warung Sarapan Pagi Bunda Tata Menggunakan Qm For Windows Dengan Metode Linear Programming - Puspita, Rinda; Siregar, Jogi Anggita; Pasaribu, Hasyim; Ritonga, Irmayanti (Universitas Labuhanbatu, 2025)
Currently, many small and medium enterprises are facing big challenges in terms of managing the production and distribution of goods. Breakfast stallBunda Tata is a culinary business that provides various choices of breakfast menu, such as nasi lemak, regular rice and vegetable rice cake. These menus have different preferences every day, depending on customer needs and preferences. Optimizing production in the culinary business world, especially breakfast stalls, is a very important aspect to increase operational efficiency and profitability. One method that is often used to solve production optimization problems is Linear Programming (LP). In this section we will discuss several concepts related to production optimization and the application of Linear Programming in the context of the culinary business. Linear Programming is a mathematical method for solving the problem of allocating limited resources to achieve optimal goals such as maximizing profits or minimizing costs. In solving linear programming problems, a mathematical model is needed. The application of Linear Programming in culinary businesses such as breakfast stalls aims to solve problems related to raw material management, production capacity and profits. Several previous studies have shown that LP can be used effectively in optimizing production in the culinary industry. Bunda Tata's Breakfast Shop wants to maximize profits with QM for Windows, a software used for data analysis and mathematical modeling.